Evaluating the implementation of PROMs and PREMs in routine clinical care: co-design of tools from the perspective of patients and healthcare professionals - Clara Amat-Fernandez; Yolanda Pardo; Montse Ferrer; Guillermo Bosch; Catalina Lizano-Barrantes; Renata Briseño-Diaz; Maria Vernet-Tomas; Lluís Fumadó; Marc Beisani; Dolores Redondo-Pachón; Anna Bach-Pascual; Olatz Garin; et al. (Health and Quality of Life Outcomes)
Abstract Background Implementation of patient-reported measures (PRMs) is an integral element for patient-centered models; however, there is still hardly any quantitative evidence regarding its impact in routine care settings. The objective of this study was to codesign two concise tools that allow for a standardized and longitudinal assessment of the implementation of PRMs in routine care in terms of acceptability and perceived value from the perspective of both patients and healthcare professionals. Methods A list of constructs and items to be presented, separately, to patients and healthcare professionals was created from evidence gathered through a narrative literature review. Focus groups, composed of either patients or healthcare professionals from different chronic conditions, were conducted for the co-design of independent assessments. Once agreement was reached, the content validity was examined in separate consensus meetings. Results A total of 10 patients and 10 healthcare professionals participated in the focus groups. After 7 focus groups, the PRMs Implementation Assessment Tool for patients (PRMIAT-P) was developed with 33 items in 9 constructs, and the tool for healthcare professionals (PRMIAT-HP) had 33 items in 16 constructs. Content validity was confirmed for both tools. Conclusions The perspective of patients and healthcare professionals regarding the implementation of PRMs in routine care can be evaluated quantitively with the PRMIAT tools. These tools are understandable, concise and comprehensive, and can be used in multiple settings and for different chronic conditions. They have been codesigned as a standard set to facilitate both longitudinal assessments and performing benchmarking among different initiatives.